Association between periodontal disease and prostate cancer - Nur RAS. Aji; Dahlia Herawati (Journal of Dentomaxillofacial Science, 2019)
Objective: The aim of this literature review was to study the underlying mechanisms of the association between Periodontal disease and Prostate Cancer.Methods: This study is literature review study, pubmed searching was used to find scientific article about association of periodontal disease and Prostate CancerResults: Study about the Association between Periodontal disease and Prostate cancer by 12-year Longitudinal Cohort Study in South Korea usingÂ  MultivariateÂ  Cox proportional Hazard Regression Analysis Periodontal Disease show a significantly and positively association with Prostrate Cancer. There may exist shared underlying genetic factors that increase the risk of both periodontal disease and cancers. Periodontitis might be associated with increased cancer risk, particularly with hematological, breast and prostate cancers. Direct correlation between periodontal disease and prostrate cancer is still unclear. It was hyphotesized that microorganisms involved in chronic periodontitis may directly induce mutations in the tumor-suppresor genes and proto-oncogenes or alter the signalling pathways that in turn stimulates cancer growthConclusion: Periodontal disease may associate to prostate cancer by mutation induction in tumor-suppresor genes.